ЖАНУБИЙ ОРОЛБЎЙИ ҚЎРИҚ ЕРЛАРИДА PANICUM MILIACEUM L. ЎСИМЛИГИНИ ЎСТИРИШ ТЕХНОЛОГИЯСИ - Қосназаров, Қ.А. (SCIENCE and SOCIETY, 2020)
The materials of this article can be used for students to write course papers, graduation papers, i.e., diploma works by bachelors, for master's theses, as well as doctoral students in their research works on this topic.
Keywords: ecological changes; food problems; fallow lands; millet; technology; suggestions; recommendations